Promoting designomic understanding among secondary school students through eco project-based learning activities module - Ghazali, Julieza (2025)
In light of social inequality, economic hardship, and environmental deterioration, the demand for sustainable development has grown increasingly pressing. Education is a crucial tactic to provide the future generation the information and abilities they need to handle these issues. The goal of this project was to encourage secondary school pupils to adopt an interdisciplinary approach called Designomic Understanding, which combines design thinking with economic principles. In order to involve students in real-world, problem-solving activities that promote creativity, critical thinking, environmental awareness, and an understanding of economic principles in the context of sustainability, the suggested framework makes use of Eco ProjectBased Learning (ECO-PBL Designomic) activities. This module was created as a learning resource to help students learn Visual Art Education. This study uses a hybrid method that integrates qualitative and quantitative data using the DDR research strategy. Students' performance on summative tests, artwork, and feedback on gallery walk activities are also evaluated in this study. In addition, the module's usability was assessed following the conclusion of the course. As a guide for creating Visual Art lesson plans and to be used in the teaching and learning process, the ECO-PBL Designomic module was developed using the ADDIE paradigm, which was backed by Lev Vygotsky's (1978) Zone of Proximal Development and Scaffolding Theory and Allan Paivio's (1971) Dual Coding Theory. Quantitative and descriptive statistics form the basis of the methods used in the data collecting. This study is supported by the qualitative methodologies' findings. Five teachers—two RBT teachers, two visual art education teachers, and one expert—as well as sixty students participated in the needs analysis portion of the study. A quasi-experimental single-group comparison design was used in the investigation. Forty pupils and one visual art teacher were purposefully chosen to participate in this phase. The findings showed that students who used the ECO-PBL Designomic module had a noticeably higher mean overall score on their summative assessments. This suggests that students' comprehension of Designomic was successfully enhanced by the ECO-PBL Designomic program. Future research directions are examined and conclusions are given.